Analysis of the Marketing Strategy for Freight Forwarding Services at the Head Office of PT Kay Ocean Indonesia in Semarang - Muhammad Imam Allaist; Ridha Aprillya Bilqis (Universitas Diponegoro, 2025)
This study analyzes the marketing strategy of PT Kay Ocean Indonesia, a freight forwarding company based in Semarang, which has experienced difficulties in consistently achieving its monthly profit targets. A qualitative descriptive approach was employed to evaluate the effectiveness of the company’s marketing strategy amid increasing industry competition. The analysis integrates Segmentation, Targeting, and Positioning (STP), the 7P service marketing mix, and SWOT Analysis. The findings reveal that the company applies geographic segmentation, targeting customers in Central Java and Yogyakarta, and positions itself as a service-oriented freight forwarder with a commitment to halal logistics certification. The 7P analysis indicates that product, place, process, and customer service are relatively well implemented, while price competitiveness, promotion, human resources, and physical evidence remain suboptimal. Furthermore, the SWOT analysis identifies key internal strengths and weaknesses, as well as external opportunities and threats that influence business performance. The study concludes that improving digital marketing, enhancing pricing strategies, and strengthening human resource capabilities are essential to increase competitiveness and achieve profit targets. These findings provide practical insights for freight forwarding companies in developing more effective marketing strategies.